Arthroscopically Guided Proximal Tibial Epiphysiodesis Screw Placement as Treatment of a Bilateral Partial Cranial Cruciate Ligament Injury in a Juvenile Dog - Olive, Mélanie; Caron, Alexandre; Fournet, Alexandre; Vanel, Maïa (VCOT Open, 2020)
This study aimed to describe surgical technique of arthroscopically guided proximal tibial epiphysiodesis screw placement in the treatment of a bilateral partial cranial cruciate ligament (CrCL) rupture in a 5.6-month-old Golden Retriever. A 19-kg, 5.6-month-old female Golden Retriever was diagnosed with bilateral partial CrCL rupture. Proximal tibial epiphysiodesis was performed bilaterally under arthroscopic guidance. Arthroscopic stifle joint inspection was performed bilaterally with a 2.7 mm arthroscope. A medial port at the level of the distal one-third of the patella was used as camera portal. A lateral instrument port was positioned at the level of the distal one-third of the patella. A 3.0 mm diameter headless cannulated self-compressive screw was placed into the centre of the tibial cranial intercondyloid area as parallel as possible to the tibial shaft axis under arthroscopic control. Screw head was buried. Arthroscopic guidance allowed good accuracy in screw placement, specifically in its insertion point. However, the screw orientation was less satisfactory. The tibial plateau angle progressively decreased in both stifles to achieve 15 degrees on the left and 16 degrees on the right at the last follow-up. A varus deformity developed on both stifles. No clinical consequences were observed. Recurrence of right pelvic lameness occurred 1 year postoperatively because of a medial meniscal lesion, which necessitated partial caudal meniscectomy. Arthroscopically guided proximal tibial epiphysiodesis is technically feasible and is a minimally invasive treatment of CrCL injury in a juvenile dog.
Keywords: arthroscopic treatment; epiphysiodesis; cruciate ligament injury; growth plate pathology; juvenile dog